A política de atendimento aos pacientes psiquiátricos em conflito com a lei no Estado do Maranhão - RODRIGUES, Paulo Guilherme Siqueira (2017)
This dissertation consists of a research on the discursive practices and the process of disinternation of people who came into conflict with the law due to serious psychological suffering, having as reference and basis the works of Michel Foucault, as well as his various commentators. The theoretical reference will be elaborated from the following works: History of the Madness in the Classical Age, Discipline and Punish: The Birth of the Prison and Microphysics of the Power. We will consider Foucault's analyzes on the treatment of insanity and governmentality in the constitution of mental health policies. It will be sought to analyze the forms of controls and the various legal technical devices that are used against persons classified as unimputable or semi-imputable. Also, we will present the different professional experiences and ananalysis of the mental health management in the State of Maranhão, based on the public policy proposals in this area, verifying the fragility of the care proposals regarding the quantity and quality of care offered In the substitutive services of mental health proposed by the Law Antimanicomial, as well as, the treatment of the madness in Brazil like process of domestication. We will adopt the bibliographic review as a research method from a descriptive character. Finally, the results obtained and the importance of establishing strategies to promote procedural and administrative speed will be presented for the effectiveness of the needs of the asylum population.